(3GdEjVGMs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s ((3NGdO YeQ Hf eMehO Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf LeYJ ai gPG GdcJGH CHhGHkG ef GdYQHjI eJMQjG LeYgG s
(3BNQgG (B:s
(3ef HGH GdEOZGe ai MQha WQa GddSGf hCUhd GdKfGjG (B: (3hPdc Cf GdVGO hGdTjf GSJWGdJG MJi GJUdJG HeNGQL gPg GdMQha Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HChd GdfSNI bQGAI GdfGSN Ydi eMeO Hf CHj GdhaG GdehUdi GdeYQha HGHf GdbUji SfI (B626 (3hgh eDda cJGH GdgGOi ai GdEYQGH ai GdChQGb GdChdi JeRjb bdjds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B200s
Keywords: (3GdfMhs